Mechanical Study on using of ACCR Thermal Conductor at 500 kV SUTET - Prasetyono, Suprihadi (Makara Journal of Technology, 2007)
Mechanical Study on using of ACCR Thermal Conductor at 500 kV SUTET. At the height of electricity demand increasing recently, circumstance of environment more limited and also expense of high investment, making thermal conductor (conductor thermal resistance) considered to be one of alternative in the electricity transmission bottlenecks. These days it has been developed thermal conductor ACCR (Aluminium Conductor Composite Reinforced) which can operate with temperature up to 240oC, so that making the current carrying capacity being higher than conventional conductor. This research aimed to study load current leading to mechanical characteristic ACCR conductor included tension, length of elongation and sag of conductor. Its expected to be good for develop in construction structure of transmission line which is appropriate to ACCR conductor characteristic. Based on this research it can be concluded that application of ACCR conductor improves transmission line capacities by 100 % on existing ROW and tower.